Peningkatan Kapasitas Peternak melalui Edukasi Budidaya Kambing Peranakan Etawa dan Saanen di Asosiasi Trasne Putra Lombok - Ine Karni; Ica Ayu Wandira; Muhammad Dohi; Eva Amalia Pertiwi; Aminurrahman; Rezki Amalyadi; Muhamad Ali; Khairil Anwar; Lalu Unsunnidhal; Ryan Aryadin Putra; Luluk Lailatun Nurjanah (Jurnal Pengabdian Magister Pendidikan IPA, 2026)
Goat farming has significant potential to support community economic development, especially through the development of Etawa Crossbreed (PE) and Saanen goats as dairy livestock. However, farmers in the Trasne Putra Lombok Farmer-Livestock Association still face limited knowledge of proper dairy goat farming, particularly in feed management, housing sanitation, animal health, and reproduction. This community service activity aimed to improve farmers’ capacity through education on PE and Saanen goat farming to support livestock productivity optimization. The activity was conducted through four stages: observation and problem identification, socialization, counseling, and evaluation. Counseling was carried out using interactive lectures, discussions, and question-and-answer sessions. The materials covered the characteristics of PE and Saanen goats, feed management, maintenance systems, housing sanitation, animal health, and basic reproductive management. The results showed that farmers gained better understanding of the basic principles of proper dairy goat farming. Farmers also showed interest in developing Saanen goats as dairy livestock. This activity serves as an initial step in improving farmers’ capacity and developing dairy goat farming in a more directed and sustainable manner.